Where did Brazilians get their diabetes drugs during the COVID-19 pandemic? DIABETESvid results - Oliveira, Rinaldo Eduardo Machado de; Franco, Laercio Joel; Teixeira, Carla Regina de Souza; Binhardi, Bárbara Aparecida; Junior, Francisco Barbosa; Melo, Karla Fabiana Santana de; Pititto, Bianca de Almeida (O Mundo da Saúde, 2022)
Access to diabetes medications is critical to disease control. However, social distancing in the COVID-19 pandemic may have limited the provision of medicines and supplies. Thus, the objective of this study was to analyze the sources of obtaining diabetes drugs in the COVID-19 pandemic in Brazil. The data came from the DIABETESvid survey, and this analysis considered a convenience sample of 1608 participants who responded to the questionnaire published on social media of scientific societies related to diabetes. This is a cross-sectional study, conducted in the form of a web survey, from September 1 to October 19, 2020. The outcome analyzed was the sources for obtaining diabetes drugs categorized in pharmacies of the "Sistema Único de Saúde", pharmacies of the “Aqui tem Farmácia Popular” program, as well as private pharmacies and drugstores and other sources. Most participants self-reported a diagnosis of type 1 diabetes mellitus (49.8%), used insulin (61.9%), and had a private health plan (68.7%). Private pharmacies and drugstores and other sources were the main places where medicines for diabetes were supplied (47.5%). Participants residing in the Midwest region of the country had a lower frequency of supply in pharmacies in the “Aqui tem Farmácia Popular” program (0.57; 95%CI 0.36-0.92). In the studied sample, there was a higher frequency of supply of diabetes drugs in private pharmacies and drugstores and other sources with a reduction in frequency in public pharmacies during the COVID-19 pandemic in Brazil.